Synergetic and performance characteristics of a high-speed pre-cooled propulsion concept - Chatzistefanou, Athanasios; Tsentis, Spyros; Kalfas, Anestis I. (ASME, 2025)
Pre-cooled air-breathing cycles are promising candidates to power future high-speed flight as well as Single-Stage-To-Orbit vehicles, due to their increased efficiency over contemporary propulsion systems and launch vehicles. These concepts usually feature complex interactions in the synergy of their thermodynamic cycles. In this study, a performance model of such a cycle is developed for its air-breathing mode of operation. One-dimensional thermodynamic modeling is employed within a component-level approach, to evaluate the performance and operation of the cycle under investigation in the range of 1.35 = ≤ 8 = 5 and conditions of up to 26 kilometers altitude. The model is validated quantitatively and qualitatively for both design and off-design conditions. The specific impulse Isp and specific thrust, as predicted by the model, agree within less than 5% for both design and off-design point conditions, while it captures the trend of Isp for the range modeled. Moreover the maximum gross thrust point is predicted correctly at M∞ = 4. The fundamental operating principles and synergetic characteristics of the engine at design and off-design conditions are investigated and reported. A model which does not feature a bypass duct is created and compared for the same inflow conditions and mission profile. It is found that the engine without the bypass duct exhibits reduced specific impulse up to 32% lower at off-design conditions while the overall trend of engine efficiency cannot be properly captured without modeling of the bypass duct, especially at the region of M∞ < 3.5.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; Energy; 4004 Chemical engineering